Evaluation of open and distance learning appying possibilities for scoolchildren extracurricuium education - Kaklauskas, Liudvikas (Lietuvos matematikos rinkinys, 2000)
Distance learning is one of the new teaching ways that is used in Lithuania. Šiauliai University has several correspondence courses for schoolchildren. Using some distance learning forms it is possible to make easer the communication between lecturers and schoolchildren. Speaking to ascertain the applying possibilities of this new teaching way, the research was carried out. The results of questionnaire corroborated that the most of schoolchildren taking correspondence course at Siauliai University are ready to use new informational technologies.